p53, estrogen and progesterone receptors in diagnostic curettage for endometrial adenocarcinoma and their correlation with morphological data and disease stage at hysterectomy - Bonfitto, Vera Lúcia Leite; Andrade, Liliana Aparecida Lucci De Angelo (São Paulo Medical Journal, 2003)
CONTEXT: Diagnostic staging is an important prognostic factor for endometrial adenocarcinoma. Apart from the histological type and histological grade, some markers seem to be associated with the stage and biological behavior of the disease. Among these are p53, estrogen and progesterone receptors. OBJECTIVE: The objectives of the present study were: to compare histological type and grading of endometrial carcinoma in curettage and hysterectomy samples; to assess expression of p53, estrogen and progesterone receptors in curettage specimens; and to correlate these data with morphology and staging of the disease in hysterectomy specimens. TYPE OF STUDY: Retrospective. SETTING: Department of Pathology, Faculdade de Ciências Médicas, Universidade Estadual de Campinas. SAMPLE: Histological diagnosis from 51 consecutive files. PROCEDURES: Immunohistochemical reactions for p53, estrogen and progesterone receptors via the avidinbiotin-peroxidase method in 51 curettage samples endometrial carcinoma were compared with the morphological data and disease stage in hysterectomy. Marker expression was correlated with histological type and grade and the final stage of the disease. RESULTS: According to the histological type: 44 cases (86%) were of endometrioid and 7 (14%) non-endometrioid carcinoma. p53 expression was observed in 16% of endometrioid and 71% of non-endometrioid cases (p < 0.05). Although estrogen expression was more evident in endometrioid (54%) than non-endometrioid cases (29%), this was not statistically significant. Progesterone receptor expression was significantly higher in endometrioid than non-endometrioid cases (70% vs. 14%, p < 0.05). According to the histological grade: Estrogen and progesterone receptors were expressed more frequently in grade I endometrioid carcinoma, while p53 was mainly reported in tumor grades II and III. According to final disease stage: p53 and estrogen expression in curettage specimens was not related to stage; progesterone receptors, however, were expressed significantly less in advanced disease. CONCLUSION: p53 was observed in the majority of nonendometrioid and in high-grade endometrioid carcinoma, but was not related to stage. Estrogen and progesterone receptors were mainly found in grade I endometrioid carcinoma. The markers studied in curettage were no more valuable for predicting the disease stage than classical histological criteria.